The Importance of A Multistakeholder Perspective in Mapping Stakeholders' Roles Toward City Branding Implementation - Forina Lestari; Melasutra Md Dali; Norbani Che-Ha (Policy & Governance Review, 2022)
This study aims to examine the perception of multi-stakeholder in implementing city branding programs and how they can collaborate across actors to support the implementation of city branding. The importance of stakeholders in implementing city branding has been widely discussed. However, the relationship between multi-stakeholder tourism is still under-explored. Therefore, this study emphasises the importance of multi-stakeholder perceptions in determining how each stakeholder can influence campaign implementation. This study uses a qualitative method by conducting in-depth interviews with relevant stakeholders: the government, the private sector, destination management staff, tourism associations, academics, and the general public. Using the Jakarta branding campaign, Enjoy Jakarta, this study finds that several crucial factors influence the Enjoy Jakarta campaign. These factors are stakeholder collaboration, departmental coordination, public management, attraction, promotion and accessibility. This study proposes stakeholders' role mapping in improving the implementation of Enjoy Jakarta programs.